Interaction of diphtheria toxin fragment A and of elongation factor 2 with Cibacron blue. Issue 9 (September 1987) - Rambelli, Fioretta; Brigotti, Maurizio; Sperti, Simonetta; Montanaro, Lucio
Abstract : Diphtheria toxin fragment A interacts with Cibacron blue in solution, although it is not retained by blue Sepharose columns. Difference spectral titration of fragment A with the dye gives a dissociation constant of the order of 10 −5 M and a 1:1 stoichiometry for the complex. In equilibrium dialysis experiments Cibacron blue behaves as a competitive inhibitor of the binding of NAD to diphtheria toxin fragment A. The dye inhibits in a non-competitive way the fragment A-catalysed transfer of ADP-ribose from NAD to elongation factor 2 (EF2). By affinity chromatography on blue Sepharose a binding of EF2 and of ADP-ribosyl-EF2 with the dye is also demonstrated. GDP, GTP and GDP(CH2 )P are able to displace EF2 from blue Sepharose.